-x+3=23

Simple and best practice solution for -x+3=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+3=23 equation:


Simplifying
-1x + 3 = 23

Reorder the terms:
3 + -1x = 23

Solving
3 + -1x = 23

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -1x = 23 + -3

Combine like terms: 3 + -3 = 0
0 + -1x = 23 + -3
-1x = 23 + -3

Combine like terms: 23 + -3 = 20
-1x = 20

Divide each side by '-1'.
x = -20

Simplifying
x = -20

See similar equations:

| -2x-6=16 | | x^3-12= | | 7x-(3x+6)=5x-47 | | 5x^2+1=2x | | 2y^3-7y^2+3=0 | | 50x^2+1=2x | | 6x-7x-5=0 | | 16x-282=6x-12 | | 52-6x=12x+18 | | 9x-(7x+2)=3x-22 | | 6x+22=16x-98 | | 3x^2+2x-40=0 | | 3x^2+58x-40=0 | | 3x^2+119x-40=0 | | x^2+25x-24=0 | | 2x+125=6x+93 | | (x)(x+1)(x+2)=720 | | 2x+25=6x+93 | | 3x^2-29x-10=0 | | x^4-4x^2+12x+9= | | x^4-4x^2+12x+9=0 | | 3x+2.3=5x+1.7 | | (3x-2)(x^2-6x+1)=0 | | a*12=b | | 5x+15=70 | | 4x^2-300=0 | | X+y=3x-5 | | 8x-7=7x-5 | | 8x=16.8 | | 7x=24.5 | | 3.4x=17 | | x^2+23=10x |

Equations solver categories